Isotopic composition and major ion concentrations of national and international bottled waters in Costa Rica - Sanchez-Murillo, Ricardo (2021)
Global bottled water consumption has largely increased (14.35 billion gallons in 2020) [1], [2], [3], [4], [5] during the last decade since consumers are demanding healthier and safer forms of rehydration. Bottled water sources are normally labeled as mountainous and pristine mineral springs (fed by rainfall and snow/glacier melting processes), deep groundwater wells or industrial purified water. The advent of numerous international and national-based bottled water brands has simultaneously raised a worldwide awareness related to the water source and chemical content traceability [6]. Here, we present the first database of stable isotope compositions and reported chemical concentrations from imported and national-based bottled waters in Costa Rica. In total, 45 bottled waters produced in Costa Rica and 31 imported from USA, Europe, Oceania, and other countries of Central America were analyzed for δ18O, δ2H, and d-excess. Chemical compositions were obtained from available bottle labels. National-based bottle waters ranged from -2.47‰ to -10.65‰ in δ18O and from -10.4‰ to -78.0‰ in δ2H, while d-excess varied from +4.2‰ up to +17.0‰. International bottle waters ranged between -2.21‰ and -11.03‰ in δ18O and from -11.3‰ up to -76.0‰ in δ2H, while d-excess varied from +5.0‰ up to +19.1‰. In Costa Rica, only 19% of the brands reported chemical parameters such as Na+, K+, Ca+2, Mg+2, F−, Cl−, NO3−, SO4−2, CO3−2, SiO2, dry residue, and pH; whereas 27% of the international products reported similar parameters. The absence of specific geographic coordinates or water source origin limited a spatial analysis to validate bottled water isotope compositions versus available isoscapes in Costa Rica [7]. This database highlights the potential and relevance of the use of water stable isotope compositions to improve the traceability of bottled water sources and the urgent need of more robust legislation in order to provide detailed information (i.e., water source, chemical composition, purification processes) to the final consumers.